Hyaluronate Protects From Benzalkonium Chloride-Induced Ocular Surface Toxicity - Vereertbrugghen, Alexia (2024)
Purpose: The purpose of this study was to investigate the effect of sodium hyaluronate (SH) on benzalkonium chloride (BAK)-induced toxicity in the ocular surface epithelium and corneal nerves. Methods: Ocular surface epithelial cells from Balb/c mice were cultured with 0.1% to 0.4% SH and 0.001% to 0.01% BAK and their metabolic activity, viability, and wound repair capacity were assessed in vitro. Following a controlled corneal wound, reepithelialization and recovery of epithelial barrier function and mechanosensitivity were measured in Balb/c mice treated with 0.4% SH 3 times/day and 0.01% BAK twice daily for 3 weeks. Nerve morphology was assessed by confocal microscopy of corneal whole mounts. Results: Whereas BAK exposure reduced metabolic activity, viability, and wound repair ability of ocular epithelial cells in vitro, pretreatment with SH ameliorated BAK toxicity in a concentration-dependent manner. The highest SH concentration partially reversed the effects of 0.01% BAK in vitro and increased the corneal healing rate of BAK-exposed mice. Although all corneal wounds closed after 4 days, continuous SH treatment improved corneal barrier dysfunction 18 days after wounding and accelerated the recovery of corneal mechanical sensitivity to baseline levels in BAK-exposed mice. SH treatment also increased corneal nerve density in the wounded area after 3 weeks. Conclusions: SH mitigates BAK-associated ocular epithelial and neurotoxicity in a concentration-dependent manner. Translational Relevance: Commercially available, high-concentration SH formulations may have added benefits in treating BAK-associated ocular surface toxicity.